Double Burden of Malnutrition among Undergraduates in Ogun State Nigeria - Catherine Adebukola Oladoyinbo; Nkereuwem N Ekerette (International Journal of Public Health Science (IJPHS), 2015)
Coexistence of under and over nutrition among the same population group is referred to as the double burden of malnutrition. The objective of this study was to assess double burden of malnutrition among undergraduate students in Ogun State Nigeria. A cross-sectional study involving 1,115 (37.8%) males and 1,835 (62.2%) females was conducted.  Body mass index (BMI) was derived from weight and a height measurement, waist circumference (WC) measurement was taken to assess abdominal obesity. SPSS version 16 was used for data analysis. Mean age, height, weight and BMI were 23±0.05years, 1.63±0.001m, 60.99±0.22kg and 22.80±0.08kgm respectively. Mean WC was 82.21±0.32cm and 80.55±0.49cm among males and females respectively. Based on BMI, the Prevalence of underweight, overweight and obesity were 13.4%, 16.9% and 7.5% respectively. BMI did not relate significantly with both age (p=0.464) and gender (P=0.115). About fifty percent (50.64%) of females and 12.36% males who were overweight and obese also had excess abdominal fat. Prevalence of abdominal obesity was significantly higher among females (16.9%) than males (2.5%), (p=0.001). Respondents in this study were faced with problems of both under-nutrition and over-nutrition.